Evidence Basis for the Use of Ultrasound for Upper-Extremity Blocks. (1st February 2010) - McCartney, Colin J.L.; Lin, Lisa; Shastri, Uma
Abstract : This article qualitatively assesses and summarizes randomized, controlled studies regarding benefits of ultrasound (US) for brachial plexus block and also examines those studies that have compared different brachial plexus block techniques using US. Studies were identified by a search of PUBMED and EMBASE databases using the MeSH terms anesthetic techniques, brachial plexus, and ultrasound . Included studies were limited to randomized trials that compared a US technique with another accepted method of performing brachial plexus block or those studies that compared 2 different US-guided techniques. Studies were further classified according to methodological quality using accepted methods. Quality scores were compared using Mann-Whitney U test, and significance assumed at P < 0.05. Twenty-five studies met inclusion criteria, with 19 studies comparing US techniques with other nerve location methods and 6 studies comparing different US techniques. Of the former, there was convincing evidence to support the use of US, with 15 of 19 studies demonstrating improved outcomes compared with existing techniques. Ultrasound provides significant advantages when performing brachial plexus block including faster sensory block onset and greater block success.